Penilaian Kualitas Visual Kawasan Wisata Alam Bantimurung Maros Sulawesi Selatan - Fawwas Ahmad Gulam Faisal; Lury Sevita Yusiana; Devvy Alvionita Fitriana (Jurnal Arsitektur Lansekap, 2025)
The Bantimurung Natural Tourism Area (NTA) in Maros Regency, South Sulawesi, is recognized as a tourist destination featuring stunning natural beauty and significant visual appeal. The region spans 48.6 hectares and features several attractions, such as karst structures, caves, unusual flora and animals, and butterfly museum. The municipal government-initiated tourism development in the 2000s by providing supporting amenities. This research evaluated the visual quality of photographic locations in Bantimurung NTA utilizing the Scenic Beauty Estimation (SBE) methodology. Data collection was conducted via questionnaires and photographic documentation. The data were assessed utilizing the SBE method to determine the visual quality of the landscape. The findings indicate that landscapes with low visual quality are dominated by artificial elements while landscapes with high visual quality are dominated by natural elements with their own uniqueness. Alternative development concept is offered for the photo spots based on their visual value assessment. Improved landscape management and accessibility to photographic locations are anticipated to augment the appeal of Bantimurung NTA as a tourist destination.